Modelling regional labour market dynamics: Participation, employment and migration decisions in a spatial CGE model for the EU - Damiaan Persyn; Wouter Torfs; d’Artis Kancs (Investigaciones Regionales - Journal of Regional Research, 2014)
This paper outlines how regional labour market adjustments to macroeconomic and policy shocks are modelled in RHOMOLO through participation, employment and migration decisions of workers. RHOMOLO, being a multisectoral, inter-regional general equilibrium model, is complex both in terms of its dimensionality and the modelling of spatial interactions through trade flows and factor mobility. The modelling of the labour market is therefore constrained by the tractability and computational solvability of the model. The labour market module consists of individual labour participation decisions, including the extensive margin (to participate or not) and the intensive margin (hours of work). Unemployment is determined through a wage curve and inter-regional labour migration decisions are modelled in a discrete-choice framework, with backward-looking expectations.